Unwilling to Train? Firm Responses to the Colombian Apprenticeship Regulation - Santiago Caicedo; Miguel Espinosa; Arthur Seibold (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We study firm responses to a large-scale change in apprenticeship regulation in Colombia. The reform requires firms to train, setting apprentice quotas that vary discontinuously in firm size. We document strong heterogeneity in responses across sectors, where firms in sectors with high skill requirements tend to avoid training apprentices, while firms in low-skill sectors seek apprentices. Guided by these reduced-form findings, we structurally estimate firms' training costs. Especially in high-skill sectors, many firms face large training costs, limiting their willingness to train apprentices. Yet, we find substantial overall benefits of expanding apprenticeship training, in particular when the supply of trained workers increases in general equilibrium. Finally, we show that counterfactual policies that take into account heterogeneity across sectors can deliver similar benefits from training while inducing less distortions in the firm-size distribution and in the allocation of resources across sectors.
Keywords: E24; J21; J24; M50; 330